Development Of A Peptide-Based System For Delivery Of Cas9:Sgrna Complexes Into Arabidopsis Thaliana - Ng, Kiaw Kiaw (2017)
Nowadays, CRISPR/Cas9 system has emerged as a powerful genome editing tool in various plant species, due to its simplicity and versatility. Typically, in plant system, Cas9 and sgNA are delivered into the plant cell in the form of DNA. However, the DNA delivery can be complicated with several problems, such as unexpected integration of exogenous DNA into plant genome, codon optimization and selection of promoter in respect to various plant species. To overcome these problems, a direct delivery system of Cas9:sgRNA complexes is needed for targeted genome editing in plants. Although there have been reports of the direct delivery Cas9:sgRNA complexes in protoplast and embryonic systems, there are no reports of the successful Cas9:sgRNA complexes delivery system in intact plant, owing to its hierarchical structures. Hence, the current study is aimed to develop a peptide-based delivery system for pre-assembled Cas9:sgRNA complexes into intact Arabidopsis thaliana for targeted genome editing.